Crop Regulation in Pomegranate (Punica granatum L.) through Induced Water Stress and Ethrel Application - Kumar, R.; Saroj, P. L.; Sharma, B. D. (International Journal of Bio-resource and Stress Management, 2021)
The present investigation was carried out at ICAR-CIAH, Bikaner, Rajasthan, India during 2017 to 2019 to regulate crop production in pomegranate at the desired period with higher number of bisexual flower for higher quality fruit yield and to minimize fruit splitting through water stress, pruning and ethrel application. Pooled data analysis revealed that horticultural interventions, chemical treatments and their interactions significantly improved plant volume, bisexual flower number, maturity index, fruit yield with significant reduction in fruit splitting, mite and fungal spot incidence. Among different treatment combinations, maximum canopy volume, number of bisexual flowers, maturity index, fruit yield and lower fruit splitting were recorded (8.56 m3, 85.11 plant-1, 47.81, 124.01 q ha-1 and 1.87 kg plant-1) in withholding irrigation during June+pruning+thinning+ethrel 2 ml l-1 as compared to absolute control (3.41 m3, 75.62 plant-1, 33.35, 85.66 q ha-1 and 2.41 kg plant-1), respectively. The mite and fungal spot incidence were recorded minimum (4.72 and 8.50%) in withholding irrigation during June+pruning+thinning+ethrel 3 ml l-1 application in comparison to maximum recorded in absolute control (29.73 and 33.68%), respectively. Therefore, it can be concluded that withholding irrigation during June+pruning+thinning with ethrel 2 ml l-1 treatment significantly improved quality fruit yield with higher number of bisexual flowers and reduced fruit splitting through induction of flowering and fruit growth during optimal climatic conditions.